Schistosomus reflexus in a feline: case report - Patiño, A. (2020)
The case of a 5-year-old crossbred female cat in her first gestation was presented for consultation. The cat had a stillborn present in the birth canal, which was extracted manually. A second puppy is expelled alive but was euthanized because of her clinical infeasibility. The two puppies presented a malformation in the abdominal region with exposure of some viscera, considered as Schistosomus reflexus syndrome. The radiological and necropsy diagnostic evaluation of the second puppy was performed, finding a closure defect of the abdominal midline with viscera exposure (small intestine, liver, right kidney and spleen among others). The radiological evaluation showed the eventration of abdominal organs without clear differentiation between them, kyphosis in the thoracolumbar segment, lordosis in the lumbar portion and oligodactyly in the right posterior limb.